2000
DOI: 10.1007/pl00008318
|View full text |Cite
|
Sign up to set email alerts
|

Posterior percutaneous spine instrumentation

Abstract: Eighty consecutive cases of suprafascial pedicle screw stabilization were reviewed. Intraoperative fluoroscopy aided the percutaneous screw placement after structural anterior interbody graft(s) were placed. During routine outpatient hardware removal, all intradiscal fusions were stressed via the Shanz screws under fluoroscopy. Anterior reconstruction via a mini open approach coupled with this minimally invasive posterior approach led to a 96% successful fusion rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
61
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(64 citation statements)
references
References 16 publications
2
61
0
1
Order By: Relevance
“…The rod connectors were just under the fascia with this system. The results were satisfactory with a 61% fusion rate in 8 months [9]. One year later, a novel instrument (sextant) was presented by Foley KT and Gupta SK.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The rod connectors were just under the fascia with this system. The results were satisfactory with a 61% fusion rate in 8 months [9]. One year later, a novel instrument (sextant) was presented by Foley KT and Gupta SK.…”
Section: Discussionmentioning
confidence: 94%
“…They also showed significant improvisation of the percutaneous system [8]. In 2000, Lowery and Kulkarini [9] described a more contemporary system. In their approach, insertion of the anterior interbody graft via laparoscopy was primarily performed, and the posterior percutaneous pedicle screws with rod connectors were then placed.…”
Section: Discussionmentioning
confidence: 99%
“…As proposed already in lumbar spine surgery, this might reduce the denervation of muscles and hospital stay [10,16,21,22,38,44] and reduces the increased complication rate following posterior or combined anterior-posterior approaches [37]. The disadvantage of the technique clearly resulted from stabilization-only character, which limits the indications.…”
Section: Discussionmentioning
confidence: 98%
“…These posterior instrumentation procedures have been shown to be associated with increased postoperative complications [37,43]. Similar to stabilization procedures of the thoracolumbar spine, which have been proposed to reduce access-related morbidity as muscular denervation, atrophy, length of hospital stay, blood loss and postoperative pain [16,21,22], minimally invasive procedures for posterior cervical instrumentation represent the next logical step. Therefore, several authors reported minimally invasive posterior procedures for stabilization and decompression of the cervical spine [5,8,33,40,45]; however, the long-term benefit on clinical outcome remains to be proven.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation